Analisis Pengaruh Praktek Total Quality Management (TQM), Terhadap Kinerja Bisnis dan Kepuasan Konsumen (Pada Sentra Industri Gerabah Kasongan Kabupaten Bantul, Yogyakarta) - Wahyuningsih, Tri; Liestyana, Yuli; Dewi, Lenny Fitriana (Jurnal Manajemen Bisnis, 2010)
Total Quality Management (TQM) was a whole apporch and a part of high level strategy. The system worked horizontally across fuctions and department, involved all employees form hight to low lavel management, included supply chain and customers. The reasearch analyzed the effect of TQM pravtices on business performance and customer satisfaction in industry of Kasongan, Bantul. Simple regression analysis used to test the effect of TQM practies on business performance and customer satisfaction partially. The result showed that TQM practies had positive significant effect on business performance, TQM practies had positive significanly effect on customer satisfaction had positive significantly effect on business performance. So, three hypothesis of the study were supported